2022
DOI: 10.1016/j.cmi.2021.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, evolution and cryptic susceptibility of methicillin-resistant Staphylococcus aureus in China: a whole-genome-based survey

Abstract: Epidemiology, evolution and cryptic susceptibility of methicillin-resistant Staphylococcus aureus in China: a whole-genome-based survey,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 23 publications
2
34
1
Order By: Relevance
“…In this study, CC59-ST59, CC5-ST5/ST764 and CC8-ST239 were the key lineages responsible for mediating the development of the methicillin resistance in S. aureus in clinical environment in China [ 9 ]. The HA-MRSA CC8-ST239 has been a pandemic linage circulating in many countries worldwide since the 1970s [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, CC59-ST59, CC5-ST5/ST764 and CC8-ST239 were the key lineages responsible for mediating the development of the methicillin resistance in S. aureus in clinical environment in China [ 9 ]. The HA-MRSA CC8-ST239 has been a pandemic linage circulating in many countries worldwide since the 1970s [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whole-genome sequencing allows for a comprehensive analysis of the epidemiology and genomic repertoire of S. aureus and provides in-depth insights into the evolution of particular MRSA clones [ 6 , 8 ]. While few studies have characterized extensive collections of MRSA isolates from China using whole-genome sequencing [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The associated STs shared by six of the seven loci were included into the same CCs (14). CC59, CC7, CC25, CC121, and CC398 were assigned according to previous publications (22,28,29). CC944 was assigned in this study because its associated ST, ST944, was the first reported type to the best of our knowledge.…”
Section: Mlst and Data Analysismentioning
confidence: 99%
“…Moreover, in China, the environmental origins of dominant lineages differed. Recently, ST5 and ST239 were found to be major lineages in hospital settings, whereas ST59 was mainly found in community settings (22). However, it was reported that the ST45 lineage has recently emerged in the community acquiring multiple antimicrobial resistance determinants (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…However, in the last decade, a blurring of the definition between CA-MRSA and HA-MRSA has been observed. CA-MRSA has gradually gained a foothold in health care settings, and the more susceptible CA-MRSA clones have gradually replaced the multiresistant HA-MRSA lineages in several countries, including China ( 7 11 ). This indicates that the epidemiological dynamics of MRSA is associated with the increasing transmission of CA-MRSA strains in health care settings.…”
Section: Introductionmentioning
confidence: 99%